Vitrectomy for Idiopathic Macular Hole in Patients Aged 80 Years or Older: Efficacy and Safety. (2nd June 2020) - Wang, Jin; Li, Qingjian; Jiang, Jing; Che, Xin; Qian, Yiwen; Zhou, Xianjin; Zhang, Yu; Wang, Zhiliang
ABSTRACT: Purpose : To assess the efficacy and safety of idiopathic macular hole (MH) surgery in elderly patients (≥ 80 years of age). Methods : Prospective study enrolled consecutive patients who underwent pars plana vitrectomy (PPV) with internal limiting membrane (ILM) peeling under retrobulbar anesthesia between February 2016 and May 2018. Twenty-eight eyes of 28 patients aged 80 years or older were classified into the elderly group, a matched group of 56 eyes from 56 younger patients as the control group. The main outcome measures included best-corrected visual acuity (BCVA) and intraoperative and postoperative complications. Results : Statistically, there was no significant difference in visual acuity improvement and incidences of complications between the elderly group and the control group ( p = .784 and p = .712, respectively). No operation in either group was postponed or canceled due to complications associated with retrobulbar anesthesia, or physical discomfort before and during the operation. Moreover, no case suffered from myocardial infarction, stroke or death during the perioperative period. Except for one case of retinal detachment postoperatively in the control group, no case required a secondary surgery. All complications were successfully resolved or managed. Conclusions : The results from our study indicate the efficacy and safety of vitrectomy for idiopathic macular hole in patients aged 80 years or older, and idiopathic MH surgery should not be denied on basis of patient age alone.